Classic and current opinion in embryonic organ transplantation - Hammerman, Marc R. (2014)
PURPOSE OF REVIEW: Here, we review the rationale for the use of organs from embryonic donors, antecedent investigations and recent work from our own laboratory exploring the utility for transplantation of embryonic kidney and pancreas as an organ replacement therapy. RECENT FINDINGS: Ultra structurally precise kidneys differentiate in situ in rats following xenotransplantation in mesentery of embryonic pig renal primordia. The developing organ attracts its blood supply from the host. Engraftment of pig renal primordia requires host immune suppression. However, insulin-producing cells originating from embryonic pig pancreas obtained very early following initiation of organogenesis [embryonic day 28 (E28)] engraft long term in non-immune suppressed diabetic rats or rhesus macaques. Engraftment of morphologically similar cells originating from adult porcine islets of Langerhans occurs in animals previously transplanted with E28 pig pancreatic primordia. SUMMARY: Organ primordia engraft, attract a host vasculature and differentiate following transplantation to ectopic sites. Attempts have been made to exploit these characteristics to achieve clinically relevant endpoints for end-stage renal disease and diabetes mellitus using animal models. We and others have focused on use of the embryonic pig as a donor.